Utility of a rescue endovascular therapy for the treatment of major strokes refractory to full-dose intravenous thrombolysis - Vanicek, J (The British Institute of Radiology., 2014)
OBJECTIVE: Large artery occlusion (LAO) in patients with major stroke predicts poor revascularization by intravenous thrombolysis (IVT) and more likely results in a poor outcome. We focused on the effects of intra-arterial thrombolysis (IAT) and endovascular mechanical recanalization (EMR) as rescue therapies in major strokes refractory to IVT. METHODS: A retrospective analysis of 87 patients (National Institutes of Health Stroke Scale >20), who did not respond to full-dose IVT due to LAO, was performed based on their endovascular therapy status. IAT was performed as an intraclot infusion of alteplase, and EMR was provided by the Solitaire device™ (Covidien, Dubin, Ireland). The recanalization and 3-month outcome rates after IAT/EMR were correlated with a group of patients who were scheduled to receive endovascular treatment but who underwent only IVT. RESULTS: We achieved successful recanalization by IAT and EMR in 68.7% and 76.1% of patients, respectively. Despite no significant differences in mortality between IAT and EMR, a trend towards better outcomes after IAT and a statistically significant increase for outcome-modified Rankin scale (mRS) 0–3 (45.7%) and mRS 0–2 (34.9%) after EMR was noted when compared with IVT. The degree of recanalization did not correlate with the functional results except for the good–moderate outcome after successful recanalization by EMR. CONCLUSION: EMR by the Solitaire device is a safe and beneficial method for the rescue treatment of patients with major stroke whose neurological status does not improve and who fail to recanalize the LAO after a 1-h full dose of IVT. ADVANCES IN KNOWLEDGE: The article verifies efficiency of the Solitaire device in major strokes.